Methicillin Resistance Elements in the Canine Pathogen Staphylococcus pseudintermedius and Their Association with the Peptide Toxin PSM-mec - Gordon Y. C. Cheung; Ji Hyun Lee; Ryan Liu; Sara D. Lawhon; Ching Yang; Michael Otto (MDPI AG, 2024)
Staphylococcus pseudintermedius is a frequent cause of infections in dogs. Infectious isolates of this coagulase-positive staphylococcal species are often methicillin- and multidrug-resistant, which complicates therapy. In staphylococci, methicillin resistance is encoded by determinants found on mobile genetic elements called Staphylococcal Chromosome Cassette mec (SCCmec), which, in addition to methicillin resistance factors, sometimes encode additional genes, such as further resistance factors and, rarely, virulence determinants. In this study, we analyzed SCCmec in a collection of infectious methicillin-resistant S. pseudintermedius (MRSP) isolates from predominant lineages in the United States. We found that several lineages characteristically have specific types of SCCmec elements and Agr types and harbor additional factors in their SCCmec elements that may promote virulence or affect DNA uptake. All isolates had SCCmec-encoded restriction-modification (R-M) systems of types I or II, and sequence types (STs) ST84 and ST64 had one type II and one type I R-M system, although the latter lacked a complete methylation enzyme gene. ST68 isolates also had an SCCmec-encoded CRISPR system. ST71 isolates had a psm-mec gene, which, in all but apparently Agr-dysfunctional isolates, produced a PSM-mec peptide toxin, albeit at relatively small amounts. This study gives detailed insight into the composition of SCCmec elements in infectious isolates of S. pseudintermedius and lays the genetic foundation for further efforts directed at elucidating the contribution of identified accessory SCCmec factors in impacting SCCmec-encoded and thus methicillin resistance-associated virulence and resistance to DNA uptake in this leading canine pathogen.